Neonatal pneumonia in developing countries. Issue 3 (21st April 2005) - Duke, T
Abstract : Pneumonia contributes to between 750 000 and 1.2 million neonatal deaths and an unknown number of stillbirths each year world wide. The aetiology depends on time of onset. Gram negative bacilli predominate in the first week of life, and Gram positive bacteria after that. Streptococcus pneumoniae probably causes about 25% of neonatal pneumonia. Interventions that would reduce mortality from this condition would have a large range of beneficial effects: improved maternal health, better management of other common neonatal conditions, and reduced long term childhood and adult morbidity.